Computer Networking Teaching and Learning Multimedia Education System - Goran BJELOBABA; Nikola POPOVIĆ; Ana SAVIĆ; Verica VASILJEVIĆ; Hana STEFANOVIĆ; Milena ILIĆ P. (Communications of International Proceedings, 2021)
The fifteen years of teaching the Computer Networking Course at the School of Electrical and Computer Engineering of Applied Studies in Belgrade, Serbia, raised an important issue – the issue of students having had much difficulty in understanding important theoretical concepts. To solve the problem, the RAMVER flexible multimedia system was designed and implemented. It is a unique animated and interactive environment for teaching and instructing small groups of students in the computer-based classroom. The main idea was that students would better understand complex concepts if both animations and hypertext were used at the same time and if students were organized into small groups in a more active environment.
Keywords: Multimedia Learning; Collaborative Learning; Computer Networking; Educational Technology